Study of the Diversity of Coral Reef Types and Conditions on Tidore Island, Tidore City Archipelago - Umanahu, Zulkarnain Riswan; Wahidin, Nurhalis; Ahmad, Adityawan (Agrikan Jurnal Agribisnis Perikanan, 2023)
This study aims to determine the species diversity and condition of coral reefs on Tidore Island, Tidore Islands City. This research was conducted for two months from March to April 2023. The data collection method used was Underwater Photo Transect (UPT) conducted at five observation stations with a transect length of 20 meters. The results of research at 5 observation stations showed the value of coral reef species diversity in Tidore Island ranged from 0.33 - 1.54. The diversity category is classified as low and moderate, the diversity of coral species with moderate categories is found at station 4 with the number of species found as many as 40 species and the lowest coral species diversity at station 2 with the number of coral species is 13 species. The percentage of coral reef cover on Tidore Island ranged from 18.25 - 58.76% with poor to good categories. Coral reef cover with poor category is found in station 1 and good category is found in station 2, 3, 4 and 5.